THE INFLUENCE OF LEADERSHIP, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. ASURANSI BUANA INDEPENDENT - Pamungkas, Rizki; Adinda tri buana; Vincent Nicolas; Sweeta Dewi; Dhita Adriani Rangkuti; Andrew Satria Lubis (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to evaluate and analyze the impact of leadership style, work motivation and work discipline on employee performance at PT. Buana Independent Insurance. The research method used is a quantitative descriptive approach with primary data collection through questionnaires distributed to respondents. The research population involved all employees of PT. Buana Independent Insurance as many as 119 people. The sampling technique uses the Slovin formula. The results of the study show that leadership style has a positive influence on employee performance, which is supported by a tcount value that is greater than ttable with an adequate level of significance. This results in acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). Apart from that, work motivation also has a significant positive impact on employee performance, as shown by the tcount value which exceeds the ttable value with quite high significance, so that Ha is accepted and Ho is rejected. However, work discipline has not been proven to have a significant positive influence on employee performance. In the analysis, the tcount value is lower than ttable with a significance level that is insufficient to reject the null hypothesis. Therefore, in this study, Ho was accepted while Ha was rejected. Thus, it can be concluded that at PT. Asuransi Buana Independent, leadership style and work motivation influence employee performance, while work discipline does not have a significant influence.